A multi-scale finite element method for failure analysis of three-dimensional braided composite structures. (1st February 2017) - Zhai, Junjun; Zeng, Tao; Xu, Guo-dong; Wang, Zhi-hai; Cheng, Su; Fang, Dai-ning
Abstract: This paper investigates the elastic behavior and failure strength of three-dimensional braided composites by using a multi-scale finite element method. The analyses are performed under the representative unit cell scale and tow architecture scale. The heterogeneous material structure in a RUC is modeled by the multiphase finite element method. Three special element types, called yarn element, matrix element and mixed element, are derived. The correlation between different scales is derived based on the continuum mechanics and homogenization method. Effective modulus of 3D braided composites is predicted solely from the corresponding constituent properties and braided geometrical parameters. The bending strengths are determined by the failure criteria of the components. The predicted results compare favorably with available experimental data. Parametric studies are also performed to examine the effect of braiding angle on the resulting mechanical properties. Highlights: A new multi-scale AEH model was presented to study the mechanical behavior 3D braided composite structures. The failure behavior of 3D braided composite structures was predicted by the multi-scale AEH model. The effects of braiding angle on the global bending strength of 3D braided composite structures were investigated.